Temperature Distribution Simulation of the Human Eye Exposed to Laser Radiation - Mirnezami, Seyyed Abbas; Rajaei Jafarabadi, Mahdi; Abrishami, Maryam (Journal of Lasers in Medical Sciences, 2013)
Introduction: Human eye is a sensitive part of human body with no direct protection and due to its lack of protection against the external heat waves, studying the temperature distribution of heat waves on the human eye is of utmost importance. Various lasers are widely used in medical applications such as eye surgeries. The most significant issue in the eye surgeries with laser is estimation of temperature distribution and its increase in eye tissues due to the laser radiation intensity. Experimental and invasive methods to measure the eye temperature usually have high risks. Methods: In this paper, human eye has been modeled through studying the temperature distribution of three different laser radiations, using the finite element method. We simulated human eye under 1064 nm Neodymium-Doped Yttrium Aluminium Garnet (Nd: YAG) laser, 193 nm argon fluoride (ArF) excimer laser, and 1340 nm Neodymium doped Yttrium Aluminum Perovskite (Nd: YAP) laser radiation. Results: The results show that these radiations cause temperature rise in retina, lens and cornea region, which will in turn causes serious damages to the eye tissues. Conclusion: This simulation can be a useful tool to study and predict the temperature distribution in laser radiation on the human eye and evaluate the risk involved in using laser to perform surgery.